Isolated popliteomeniscal ligament injuries in soccer players: A report of two cases - Theodorakys Marín Fermín; Peter Verdonk; Ian McGuinness; Javier Arnaiz; Marcelo Bordalo-Rodrigues; Bashir Ahmed Zikria (Journal of Orthopaedic Reports, 2023)
Background: Athletes are at higher risk of popliteomeniscal ligament (PML) injury due to sudden, repetitive, rotational knee movements when practicing sports. Damage to these ligaments leads to a hypermobile lateral meniscus, potentially locking during deep knee flexion, and persistent posterolateral knee pain. Due to the intricated anatomy of the posterolateral corner of the knee, clinical and radiologic diagnosis of isolated PML injury remains challenging, and its relevance is still questioned. This study aims to describe the clinical presentation of two soccer players that failed conservative treatment after being diagnosed with isolated PML injuries and intact lateral meniscus and required urgent surgical fixation. Case report: Two professional soccer players (31 and 16 years old) consult after experiencing an acute injury. The physical examination was normal except for posterolateral knee pain (no joint line pain, swelling, deformity, or instability). MRI examinations revealed no meniscus injury but an increased signal in the posterolateral corner of the knee and thickening of the PML fasciculi compatible with an isolated tear. Failed conservative treatment in both athletes due to lateral meniscus instability prompted arthroscopic lateral meniscus repair. Conclusion: Early arthroscopic assessment and meniscus fixation in isolated PML injuries yield good outcomes. Conservative treatment encouraged by meniscus indemnity on MRI assessment might be at risk of failure due to meniscus instability/injury and knee locking.